Un'intellettuale a metà tra due mondi : La filosofia della fotografia di Susan Sontag fra pensiero critico e attivismo politico (Balthazar, 2025)
Susan Sontag’s essays on the vast topic of photography – mainly On Photography and Regarding the Pain of Others – are significant pieces of her philosophical thought, but also shed light on the importance that political activism had in Sontag’s life, at least since the start of the Vietnam War. In the two essays, both the theoretical and the practical frameworks are outlined in detail by the American philosopher, who significantly highlights the strict bonds that tie them together. Among these threads, the experience of travel occupies a very important space, because it allows Sontag to challenge her ideas and – at the same time – put into practice her thoughts. In this sense, the present article will analyse both the ontological and the aesthetical dimensions on one side and the political and ethical ones on the other of On photography and Regarding the pain of others and will point out as well how specific travels – to Hanoi for the former work and to Sarajevo for the latter – helped Sontag shape some of the ideas she expresses in these essays, mainly regarding war photography.